2016
DOI: 10.1016/j.bbalip.2015.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a land-locked Atlantic salmon (Salmo salar L.) population as a potential genetic resource with a focus on long-chain polyunsaturated fatty acid biosynthesis

Abstract: 24The natural food for Atlantic salmon (Salmo salar) in freshwater has relatively lower levels 25 of omega-3 (n-3) long-chain polyunsaturated fatty acids (LC-PUFA) than found in prey for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
30
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 59 publications
6
30
4
Order By: Relevance
“…LA supplementation, on the contrary, increased both elovl5b transcript abundance and 20:3n-3 production. A recent study suggested that land-locked salmon, which remain in freshwater their whole life and thus are naturally surrounded by lower levels of n-3 PUFA, might have a higher ∆8 activity compared to their farmed counterparts [53]. In the present study, radioactivity recovered in 20:4n-3 was significantly reduced in the PL fraction of cells by increasing levels of n-3 VLC-PUFA, and the addition of LA reduced it further.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…LA supplementation, on the contrary, increased both elovl5b transcript abundance and 20:3n-3 production. A recent study suggested that land-locked salmon, which remain in freshwater their whole life and thus are naturally surrounded by lower levels of n-3 PUFA, might have a higher ∆8 activity compared to their farmed counterparts [53]. In the present study, radioactivity recovered in 20:4n-3 was significantly reduced in the PL fraction of cells by increasing levels of n-3 VLC-PUFA, and the addition of LA reduced it further.…”
Section: Discussionsupporting
confidence: 51%
“…Data are shown as mean ± SEM (n=6). Formatted ... [33] Formatted ... [34] Formatted ... [35] Formatted ... [36] Formatted ... [37] Formatted ... [38] Formatted ... [39] Formatted ... [40] Formatted ... [41] Formatted ... [42] Formatted ... [43] Formatted ... [44] Formatted ... [45] Formatted ... [46] Formatted ... [47] Formatted ... [48] Formatted ... [49] Formatted ... [50] Formatted ... [51] Formatted ... [52] Formatted ... [53] Formatted ... [54] Formatted ... [55] Formatted ... [56] Formatted ... [57] Formatted ... [58] Formatted ... [59] Formatted ... [60] Formatted ... [61] F o r P e e r R e v i e w 31 Table 78. Spearman's correlation coefficients between cellular EPA or cellular DHA and 18:3n-3 and its FA products in control hepatocytes and hepatocytes supplemented with lipoic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, while the aquaculture industry seeks to further stretch the optimization of fish feed production, the administration of isotopes will provide deeper insights into the regulation of lipid storage and oxidation in fish species in response to different combination of macronutrients. This may be particularly interesting in the procurement of new species to farm or in the optimization and selection of existing ones, currently happening by trait preference (Jin et al, 2014b;Song et al, 2018) or by recurring to the wide spectrum of metabolic responses occurring in nature (Betancor et al, 2016;Marandel et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Comparing anadromous (semi-anadromous) and landlocked conspecific fish, it should be taken in account that land-locked populations may have a higher capacity of biosynthesis (conversion) of long-chain PUFA, EPA and DHA from short-chain n-3 precursor FA compared to that of anadromous populations [71,72]. For instance, this putative ability might partly explain the higher EPA + DHA content of land-locked C. lavaretus from the Sobachye Lake vs. the lower content of migratory C. lavaretus from the Keret River.…”
Section: Discussionmentioning
confidence: 99%